EPISTEMOLOGI PENDIDIKAN ISLAM MONOKOTOMIK: MENAKAR MANAJEMEN PENDIDIKAN PARIPURNA BERBASIS RASIONALISTIK¬WAHYUISTIK - Ilyasin, Mukhammad (JURNAL AT-TURAS, 2016)
The classic problem of contemporary education today is the integration of two knowledge entities which many have positioned both as diametrical of one another, i.e. the religious knowledge (Semitic) and general knowledge (Hellenistic). This polarization later created a variant that has different form and characteristics, in terms of materials, educational systems, and organizational forms. In order to build an educational system that enables to generate the idealistic results, the management system should not be separated to philosophical rules which lie within, mostly the epistemological frame. Hence, it is important to construct the epistemology of monochotomic Islamic education and management which characterized by Islamic values. The values become the foundation of all operational functions of the management, including managing educational system efficiently and effectively. Both are the forms of philosophical Islamic education in the aspects of axiology and epistemology that could generate human who acquire scientific and technological skills as well as obedience to Islam.